(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: This study assessed the prevalence of overweight and obesity and associated factors among lower secondary school students in Tien Giang province in 2024, providing scientific evidence to support school-based obesity prevention efforts. Method: A cross-sectional design was applied to a sample of 6009 students. Anthropometric measurements (weight, height, waist and hip circumferences), blood pressure, and demographic data were collected. Nutritional status was classified according to World Health Organization criteria. Multivariable logistic regression was used to identify factors associated with overweight and obesity. Results: The prevalence of overweight, obesity, and undernutrition was 19.3%, 14.9%, and 4.8%, respectively. Overweight and obesity were more common in male students (41.9%) than in females (29.6%), and in the 11-12 age group (41.4%) compared to the 13-14 age group (29.8%). The waist-to-hip ratio was the strongest risk factor (OR = 4.22; 95%CI: 3.86-4.61). The predictive model yielded an area under the ROC curve of 0.813, indicating good discriminative ability. These findings emphasize the importance of early prevention and the need to integrate nutrition interventions into both school and family settings to reduce future cardiovascular risk. Conclusion: The prevalence of overweight and obesity in secondary school students in Tien Giang province is 34.2%. School nutrition education programs, increased physical activity, and regular monitoring of metabolic risk indicators are needed to address the public health burden of overweight and obesity in school-age children.